Empirical Relationship Between Macroeconomic Volatility and Islamic Stock Returns (Case Study on Jakarta Islamic Index within Period of 2009-2014) - Putra, Gilang Perdana; Darmansyah, Asep (Journal of Business and Management, 2015)
Abstract- Capital market as one of the promising economic instruments is the investment object that quite interesting, but still not much glimpsed by Indonesian people. Recorded only about 4% of people who know about the capital market, and based on an index of literacy in services and financial sector, the utilization rate of capital market products and services only reached 0.11%. Meanwhile, the market share of Islamic stocks has mastered 50% of the shares in the Indonesian Stock Exchange. Thus the Jakarta Islamic Index (JII) as one of sharia stock index may be a reference to an attractive investment for the Muslim majority of Indonesian people (87.18%). On the other hand, gold that has a long history and relations with the Islamic economic world is still a favorite commodity to invest. World Gold Council noted that Indonesia becomes the highest gold consumer in Southeast Asia. However, despite being one of the safest investment due to its value tends to rise, but the gold return tends to be lower than stock returns. Meanwhile the year 2009 was a year with a positive vision for the Indonesian economy after the global crisis of 2008. Various economic indicators experienced a positive trend, as inflation reached 2.78%, the lowest in the history of the Indonesian economy. As well as the performance of the Indonesian capital market, IHSG in 2009 increased by 87% from the previous year, the highest in ASEAN. By contrast, the exchange rate of has weakened against US dollar over the years, with the exception of 2010 which is capable strengthened to Rp8.900, - per US dollar. Also the nominal GDP has increased from year to year. This research aimed to determine the effect of macro-economic factors that have been mentioned, that are inflation, exchange rate and GDP, as well as the price of gold toward stock returns in companies listed in JII from 2009 to 2014. The data used in this research is the annual secondary data of each variable. By using panel data regression method, this research found that inflation, exchange rates and the gold price has a significant effect on stock returns in JII, while GDP has no significant effect. But simultaneously, all four of these variables have a significant effect and are able to explain as much as 62% of the information on the stock return of companies listed in JII, the rest of 38% is explained by other variables outside the four independent variables in this research. This research is also expected can give consideration to investors who want to invest in the capital market, especially Islamic stock in JII.Â Keywords: capital market, stock returns, inflation, exchange rates, gross domestic product, the price of gold, panel data regression, Jakarta Islamic Index